Câmiü't-Tevârîh’in Taşkent Nüshâsında Han ve Hatun Sultan Başlıkları Üzerine Değerlendirme - Akay, Gulzoda Makhmudjonova; Ayaz, Büşra; Lei, Chuanyi (Ege Üniversitesi, 2024)
İslam dünyasında resimli tarih eserlerinin gün yüzüne çıkması 14. yüzyılın başlarına tekabül eder. Aynı yüzyılda genel dünya tarihini, İslam öncesi ve sonrasındaki peygamber ve meliklerinin hayatını içeren önemli eserler de gün yüzüne çıkar. İlhanlı hakimiyeti altında başlatılan bu tarih metni oluşturma çalışmaları bir sonraki yüzyıllar için örnek niteliğini taşır. Resimli tarih eserlerine öncülük eden Câmiʿu’t-Tevârîḫ’in, İlhanlı dönemi sonunda bir müddet tarih sahnesinden kaybolduğu görülür. Eserin yeniden hayat bulması ise Timurlu hakimiyeti dönemine tekabül eder. Timur sonrasında yeni hükümdar Sultan Şâhruh döneminde genel dünya tarihini içeren metinler önemsenmeye başlanır. Saray tarihçisi Hâfız-i Ebrû tarafından saray kitaplığında özenle toplanmaya başlanan Câmiʿu’t-Tevârîḫ’in nüshaları, Timurlu sarayında hazırlanan genel dünya tarihini içeren resimli nüshaların oluşumuna öncülük eder. Bu çalışma Câmiʿu’t-Tevârîḫ’in Özbekistan Cumhuriyeti Bilimler Akademisi Ebü’r-Reyhân Bîrûnî Doğu Araştırmalar Enstitüsünde, N. 1620 numaralı nüshadaki Han ve Hatun sultan başlıkları üzerine kurgulanmıştır. İlhanlılar döneminde kıyafet, toplumsal statünün anlaşılmasında önemli bir göstergedir. Buna bağlı olarak da sultanların kıyafet ve başlıkları onların en önemli temsil gücü haline gelir. Dolayısı ile resimli yazmalarda han ve hatunlar dikkat çekici figürlerdir. Özellikle erkek figürlerinde toplumsal hiyerarşinin yansıması, kullanılan başlıklar üzerinde kendini gösterir. Bu gelenek dönemin resim sanatında da etkisini gösterir. Hükümdar ve seleflerini betimleyen kompozisyonların içerisinde sadece soylu kesim değil, saray maiyetinde çeşitli hizmette bulunan figürlerin giysi ve başlıklarının benzerliği de dikkat çekicidir. Çalışmada Câmiʿu’t-Tevârîḫ nüshasındaki sultan başlıkları üzerinden ikonografik ve kronolojik olarak benzerlikler karşılaştırmalı analize tabi tutulmuştur. Dönemin hükümdar ve hanedan üyelerinin törenlerde kullanılmaya başladıkları belirli başlıkların, bir sonraki yüzyıllarda da kullanılmaya devam edildiği görülmektedir. Çalışmada 15. yüzyılda Timurlu saray atölyesinde yeniden derlenmeye başlanan Câmiʿu’t-Tevârîḫ nüshalarındaki taht ve tören sahnelerinin benzerliği de karşılaştırmalı analizle irdelenir. Ayrıca çalışmada hükümdar eşlerinin kullandıkları başlık biçimi ‘Bogtak’ başlığı altında kronolojik olarak kategorize edilecektir. Başlık tipolojisi üzerine yapılan benzer çalışmalara ışık tutması ön görülmüştür.

The emergence of illustrated historical works in the Islamic world corresponds to the early 14th century. In the same century, important works depicting general world history and the lives of prophets and rulers before and after Islam also come to light. The efforts to create these historical texts under the Ilkhanid rule serve as examples for the subsequent centuries. It is observed that the precursor of illustrated historical works, Jami’ al-Tawarikh, disappeared from the historical scene towards the end of the Ilkhanid period. Its revival, however, coincides with the Timurid rule. After Timur, texts encompassing general world history gain importance during the reign of the new ruler, Sultan Shahrukh. The copies of Jami’ al-Tawarikh, carefully collected in the palace library by the court historian Hafiz-i Abru, pave the way for the creation of illustrated copies containing general world history in the Timurid court. This study is based on the Khan and Khatun sultan titles found in the copy numbered N. 1620 of Jami’ al-Tawarikh and is conducted at the Institute of Eastern Studies named after Abu Rayhan Biruni of the Academy of Sciences of the Republic of Uzbekistan. Clothing played a significant role in understanding social status during the Ilkhanid period. Consequently, the clothing and headgear of sultans became their most important symbols of representation. Therefore, Khan and Khatun figures are prominent in illustrated manuscripts. Particularly in male figures, the reflection of social hierarchy is evident in the headgear used. This tradition also influences the art of painting during the period. The similarity in the clothing and headgear of not only the noble class but also the various figures serving in the palace entourage is remarkable. This continuity indicates the popularization of the tradition by artists in the next period. Thus, it facilitates the analysis of the position of the figures in the composition concerning the text-image relationship. Such depictions provide significant information about the economy, social structure, societal perception, and the involvement of women in social life during the period. The figures of the sultan’s consorts seated on the throne together with the ruler symbolize the conditions of the era in terms of social status. Accordingly, a comparative analysis is conducted on the similarities between the sultan titles in Jami’ al-Tawarikh’s copy numbered N. 1620, which is believed to have been compiled in the Timurid court workshop centered in Herat in the 15th century, in terms of iconography and chronology. It is observed that certain specific headgear worn by rulers and members of the dynasty during ceremonies in the 14th-century manuscript continued to be used in the subsequent centuries. The similarity in throne and ceremonial scenes in the copies of Jami’ al-Tawarikh compiled in the Timurid court workshop in the 15th century is also analyzed through comparative analysis. Additionally, the headgear used by the rulers’ consorts will be categorized chronologically under the title of ‘Boghtagh’. Through the analysis of the headgear of Khan and consorts in the illustrations of Jami’ al-Tawarikh, this study aims to shed light on the status and social position of women in the Ilkhanid and Timurid periods and contribute to similar studies conducted on the typology of headgear worn by consorts.
An Evaluation on The Khan and Khatun Sultan Headdresses in The Tashkent Copy of Jamı’ Al-Tawarikh
Keywords: Câmiʿu’t-Tevârîḫ; İlhanlılar Dönemi; Timurlu; Bogtak; Sultan Başlıkları; Jami’ al-Tawarikh; Ilkhanid Period; Timurid; Boghtagh; Sultan Headdresses